The Organizational Economics of School Chains - Lorenzo Neri; Elisabetta Pasini; Olmo Silva (Institute of Labor Economics (IZA), 2022)
Although school autonomy is often advocated as a way to improve student achievement, many countries are experiencing a counterbalancing trend: the emergence of `chains' that bind schools together into structures with varying degrees of centralization. Despite their prominence, no evidence exists on the determinants and effects of differences in the organizational set-up of school chains. Our work aims to fill this gap. We use some of the key insights of the organizational economics of firms to study the organization of school chains. We match survey information on decentralization decisions of procurement activities for approximately 400 chains and 2,000 schools in England to student-, school and market-level administrative records. We find that chains with a larger share of schools whose leadership background is aligned with the chain board's expertise, younger chains, and chains that are closer to the market value-added (productivity) frontier decentralize more. We find instead no association between the value-added heterogeneity of the markets in which chains operate and their decision to delegate. We also investigate the link between the structures of chains and their students' performance. We find no association between decentralization and performance. This is consistent with the intuition that chains choose their organization in ways that maximize output (i.e., students' learning) and so the equilibrium relationship between performance and organizational set-up is flat.
Keywords: I2; L2; D8; 330; school chains; school autonomy; organizational economics; incomplete contracts